Phytochemical Screening of Cinnamon Bark (Cinnamomum burmanii) (C. Ness & T. Ness) C. Ness ex Blume Ethanol Extract and Antioxidant Activity Test with DPPH (2,2-diphenyl-1-picrylhydrazyl) Method. - Sirait, Tri Susanti; Arianto, Anayanti; Dalimunthe, Aminah (International Journal of Science, Technology & Management, 2023)
Cinnamon (Cinnamomum burmanii) is one of the spices that can be used as cosmetic preparations in the pharmaceutical industry because it contains potent antioxidants. Examples of cosmetic products containing cinnamon are body scrubs, body showers, and moisturizers. This study aimed to determine the antioxidant activity of cinnamon extract using the DPPH method. Cinnamon was extracted using the maceration technique with 96% ethanol solvent, and phytochemical screening was carried out. The results of phytochemical screening from cinnamon bark extract were alkaloids, saponins, tannins, triterpenoids, and flavonoids. Antioxidant activity obtained an IC50 value of 25.35 ppm. Based on these results, the cinnamon extract has a very strong antioxidant activity value.